(Z)‐2‐(3‐Chlorobenzylidene)‐3, 4‐dihydro‐N‐(2‐methoxyethyl)‐3‐oxo‐2H‐benzo[b][1, 4]oxazine‐6‐carboxamide as GSK‐3β inhibitor: Identification by virtual screening and its validation in enzyme‐ and cell‐based assay. (16th February 2017) - Joshi, Prashant; Gupta, Mehak; Vishwakarma, Ram A.; Kumar, Ajay; Bharate, Sandip B.
Abstract : Glycogen synthase kinase 3β (GSK‐3β) is a widely investigated molecular target for numerous diseases including Alzheimer's disease, cancer, and diabetes mellitus. The present study was aimed to discover new scaffolds for GSK‐3β inhibition, through protein structure‐guided virtual screening approach. With the availability of large number of GSK‐3β crystal structures with varying degree of RMSD in protein backbone and RMSF in side chain geometry, herein appropriate crystal structures were selected based on the characteristic ROC curve and percentage enrichment of actives. The validated docking protocol was employed to screen a library of 50, 000 small molecules using molecular docking and binding affinity calculations. Based on the GLIDE docking score, Prime MMGB/SA binding affinity, and interaction pattern analysis, the top 50 ligands were selected for GSK‐3β inhibition. (Z)‐2‐(3‐chlorobenzylidene)‐3, 4‐dihydro‐ N ‐(2‐methoxyethyl)‐3‐oxo‐2H‐benzo[b][1, 4]oxazine‐6‐carboxamide (F389‐0663, 7 ) was identified as a potent inhibitor of GSK‐3β with an IC50 value of 1.6 μm . Further, GSK‐3β inhibition activity was then investigated in cell‐based assay. The treatment of neuroblastoma N2a cells with 12.5 μm of F389‐0663 resulted in the significant increase in GSK‐3β Ser9 levels, which is indicative of the GSK‐3β inhibitory activity of a compound. The molecular dynamic simulations were carried out to understand the interactions of F389‐0663 with GSK‐3β protein. Abstract : Herein, we report identification of benzo[b][1, 4]oxazine‐6‐carboxamide class of GSK‐3beta inhibitor through virtual screening. The validation of the identified lead was demonstrated in enzyme‐ and cell‐based assays.